2007
DOI: 10.1038/sj.emboj.7601882
|View full text |Cite
|
Sign up to set email alerts
|

Hypermetabolism in mice caused by the central action of an unliganded thyroid hormone receptor α1

Abstract: Thyroid hormone, via its nuclear receptors TRalpha and TRbeta, controls metabolism by acting locally in peripheral tissues and centrally by regulating sympathetic signaling. We have defined aporeceptor regulation of metabolism by using mice heterozygous for a mutant TRalpha1 with low affinity to T3. The animals were hypermetabolic, showing strongly reduced fat depots, hyperphagia and resistance to diet-induced obesity accompanied by induction of genes involved in glucose handling and fatty acid metabolism in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 47 publications
(59 reference statements)
9
103
3
Order By: Relevance
“…Recent studies in mice have shown that suppression of TR␣1 signaling via a mutation causing a 10-fold lower affinity for T 3 enhances basal metabolism. This appeared to be mediated via increased sympathetic tone to brown adipose tissue, overriding the peripheral actions of the receptor (25). These observations suggested an important role for TR␣1 in regulating sympathetic outflow from the hypothalamus.…”
Section: Discussionmentioning
confidence: 75%
“…Recent studies in mice have shown that suppression of TR␣1 signaling via a mutation causing a 10-fold lower affinity for T 3 enhances basal metabolism. This appeared to be mediated via increased sympathetic tone to brown adipose tissue, overriding the peripheral actions of the receptor (25). These observations suggested an important role for TR␣1 in regulating sympathetic outflow from the hypothalamus.…”
Section: Discussionmentioning
confidence: 75%
“…Mice heterozygous for a point mutation in TRα1 represent an established animal model for receptor-mediated hypothyroidism (9,11). Their adult phenotype is a combination of irreversible defects caused by the defective TRα1 signaling during brain development and impairments in acute TRα1 signaling (10,12). However, as the acute impairments in TRα1 signaling can be reversed by treating the Thra1 +/m mice with T3 (11), the identification of irreversible developmental defects becomes possible.…”
Section: Discussionmentioning
confidence: 99%
“…An additional melting curve was recorded to confirm the specificity of the reaction. The primer sequences have been published previously (10) or are listed in Supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that TRα1PV dysregulates PPARγ expression which results in impaired adipogenesis of WAT in TRα1 PV/N mice. Similar to TRα1 PV/N mice, the TRα1R384C knock-in mice exhibit a lean phenotype with reduction in white fat mass and decreased leptin levels (Sjögren et al, 2007). TRα1R384C mice are hypermetabolic and resistant to diet-induced obesity.…”
Section: Regulation Of Lipid Homeostasis and Adipogenesis In White Admentioning
confidence: 98%